Um estudo do comportamento empreendedor a partir de atitudes implícitas - Marina Mendonça de Sousa (2019)
Instruments devised for entrepreneurial potential and propensity measurement are largely based on estimated frequency of particular behavioral patterns, inferred from explicit measures of self-report. The study here described proposes a more comprehensive understanding about the variables concerning the entrepreneurial propensity, considering not only the occurrence of a certain behavior, but also how this behavior is related to the symbolic relations network established in the repertoire of different individuals. Specifically, we sought to assess if individuals showing a high entrepreneurial potential, measured using the Entrepreneurial Behavioral Characteristics (CCE’s), would also show a pro-entrepreneurial bias using an implicit attitudes procedure, and, complementarily, if individuals showing a low entrepreneurial potential would demonstrate an anti-entrepreneurial bias. In this regard, an experiment was conducted with 32 undergraduates, ages ranging between 18 and 24 years, from different areas and both sexes. First, participants were divided into two distinct groups, one for those with higher scores of entrepreneurial potential, and other for those with lower scores of entrepreneurial potential, measured using a self-report questionnaire, which evaluates frequencies of those behavior considered as entrepreneurial. Thereafter, participants underwent an Implicit Relational Assessment Procedure (IRAP), which consisted in relating the word “entrepreneur” with positive and negative words. In this procedure, participants should respond in a pro-entrepreneurial way on some occasions, that is, to respond “true” for the relation between the word “entrepreneur” and a positive word, and “false” for the relation between “entrepreneur” and a negative word. On other occasions, participants should respond in an anti-entrepreneurial way, responding “true” to the relation between “entrepreneur” and a negative word, and “false” to the relation between “entrepreneur” and a positive word. The results showed that both groups had a pro-entrepreneurial bias. Thereby, those results suggest that entrepreneurial potential may not be related to the symbolic context in which the entrepreneurial behavior occurs. In addition, this is the first step towards investigating whether results obtained in IRAP could be used as an additional source of information on the entrepreneurial propensity, considering that the correspondence between this kind of behavior and positive consequences is a necessary condition to increase its frequency.